The utility of the respiratory rate-oxygenation index as a predictor of treatment response in dogs receiving high-flow nasal cannula oxygen therapy - Duble, Erin; Her, Jiwoong; Preteseille, Ingrid; Lee, Jeongmin; Allaouchiche, Bernard; Pouzot-Nevoret, Céline (Frontiers in Veterinary Science, 2024)
Objective: To evaluate the respiratory rate-oxygenation index (ROX) and the ratio of pulse oximetry saturation (SpO2) to fraction of inspired oxygen (FiO2) (SpO2/FiO2, [SF]) to determine if these indices are predictive of outcome in dogs receiving high-flow nasal cannula oxygen therapy (HFNOT).Design: Prospective observational design.Setting: Two university teaching hospitals.Animals: Eighty-eight dogs treated with HFNOT for hypoxemic respiratory failure due to various pulmonary diseases.The ROX index was defined as the SF divided by respiratory rate (RR). ROX and SF were calculated at baseline and for each hour of HFNOT. The overall success rate of HFNOT was 38% (N = 33/88). Variables predicting HFNOT success were determined using logistic regression, and the predictive power of each variable was assessed using the area under the receiver operating curve (AUC). ROX and SF were adequately predictive of HFNOT success when averaged over hours 0-16 of treatment, with similar AUCs of 0.72 (95% Confidence Interval [CI] 0.60-0.83) and 0.77 (95% CI 0.66-0.87) respectively (P < 0.05). SF showed acceptable discriminatory power in predicting HFNOT outcome at hour 7, with an AUC of 0.77 (95% CI 0.61-0.93, P = 0.013) and the optimal cut-off for predicting HFNC failure at hour 7 was SF ≤ 191 (sensitivity 83%, specificity 76%).Conclusions: These indices were easily obtained in dogs undergoing HFNOT. The results suggest that ROX and SF may have clinical utility in predicting outcomes of dogs on HFNOT. Future studies are warranted to confirm these findings in a larger number of dogs in specific disease populations.